2017
DOI: 10.4081/reumatismo.2017.935
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis with polyangiitis in Tunisia

Abstract: SUMMARYGranulomatosis with polyangiitis (GPA) is more frequent in Northern rather than Southern countries. Very few studies have been conducted in Africa. We have performed a retrospective descriptive study including clinical and laboratory profiles of 30 Tunisian GPA patients seen at the department of Internal Medicine of the University Hospital of la Rabta from 2000 to 2014. Mean age at initial GPA diagnosis was 46±12 years, and the average number of months between the onset of symptoms and diagnosis was 25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
3
4
0
2
Order By: Relevance
“…Renal involvement was present in 83.3% of patients, revealed by renal insufficiency in 83.3% of cases, proteinuria in 72% of subjects and hematuria in 55 % of cases. These clinical signs have been reported by many authors [11][12][13].…”
Section: Clinical Features Compared In Aav Diseasessupporting
confidence: 74%
“…Renal involvement was present in 83.3% of patients, revealed by renal insufficiency in 83.3% of cases, proteinuria in 72% of subjects and hematuria in 55 % of cases. These clinical signs have been reported by many authors [11][12][13].…”
Section: Clinical Features Compared In Aav Diseasessupporting
confidence: 74%
“…ENT involvement was found in 65.2% of our GPA patients, which is less than what is found in previous studies reporting 72%-99% [1,5,[13][14][15][16]. A study from Tunisia has reported initial ENT involvement of 56% and 83% at follow up [17]. Nose and sinus are reported to be affected by GPA in 55-90% of patients, which is comparable to our finding of 56.5% [8,9,16,18].…”
Section: Discussionsupporting
confidence: 55%
“…In another retrospective study (95) of 30 GPA patients conducted in Tunisia, ENT involvement was common during follow-up (83% of patients) but was rarely recognized at symptom onset (56% of patients). The renal involvement was frequent (56%) and significantly associated with poor prognosis (95). The rate of relapses was 36% and the overall 2year survival was much lower (60%) than that reported for highincome countries.…”
Section: Impact Of Ethnicity In Aav Severity and Treatment Approachmentioning
confidence: 79%